Theology's epistemological dilemma : how Karl Barth and Alvin Plantinga provide a unified response - Diller, Kevin, 1971- (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2014)
Karl Barth and Alvin Plantinga are not thought of as theological allies. Barth is famous for his opposition to philosophy's role in theology, while Plantinga is famous for his emphasis on warranted belief. Kevin Diller argues that they actually offer a unified response to the central epistemological dilemma in theology.
What Is the Epistemic Problem? -- Barth's Theology of Revelation: for Us and for Our Salvation -- Barth's Engagement with Philosophy: a Theo-foundational Epistemology -- Plantinga's Christian Philosophizing and Warrant -- Plantinga's Epistemology of Christian Belief: the Warrant of Revelation -- Summarizing Interlude: the Unified Barth/Plantinga Approach to Christian Theological Epistemology -- Theology and Reason: Natural Theology and the Reformed Objection -- Faith and Revelation: What Constitutes a Genuine Human Knowledge of God? -- Scripture and Theology: Warrant and Normativity of Scripture?
Online resource; title from PDF title page (Ebsco, viewed Jan. 28, 2015).
Includes bibliographical references and index.
Keywords: Barth, Karl, -- 1886-1968.; Plantinga, Alvin; Barth, Karl, -- 1886-1968.; Plantinga, Alvin; Philosophical theology; Philosophy and religion; Knowledge, Theory of (Religion); Christian philosophy; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Christian philosophy; Knowledge, Theory of (Religion); Philosophical theology; Philosophy and religion; Barth, Karl, -- 1886-1968.; Christian philosophy; Knowledge, Theory of (Religion).; Philosophical theology; Philosophy and religion; Plantinga, Alvin; Electronic books; Electronic books